Genotoxic effects of Roundup Full II® on lymphocytes of Chaetophractus villosus (Xenarthra, Mammalia): In vitro studies - Luaces, Juan Pablo (2017)
In Argentina, Chaetophractus villosus has a wide distribution that overlaps with agricultural areas where soybean is the predominant crop. In such areas the pesticide Roundup Full II® (RU) is widely applied. The genotoxic effect of its active ingredient glyphosate (RU is 66.2% glyphosate) on the peripheral blood lymphocytes of C. villosus was tested over a range of concentrations (280, 420, 560, 1120 μmol/L). Culture medium without glyphosate served as negative control, while medium containing mitomycin C served as positive control. Genetic damage was characterized in terms of the percentage of cells with chromosome aberrations (CA), the mean number of sister chromatid exchanges (SCE) per cell, and the modification of cell proliferation kinetics via the calculation of the replication index. Significant increases (p < 0.0001) were seen in the CA frequency and the mean number of SCEs per cell compared to negative controls at all the RU concentrations tested. Chromatid breaks, the only form of CA observed, under the 560 μmol/L RU conditions and in presence of mitomycin C were four to five times more common than at lower concentrations, while no viable cells were seen in the 1120 μmol/L treatment. The mean number of SCEs per cell was significantly higher under the 280 μmol/L RU conditions than the 420 or 560 μmol/L RU conditions; cells cultivated in the presence of MMC also showed significantly more SCEs. All the RU concentrations tested (except in the 1120 μmol/L RU treatment [no viable cells]) induced a significant reduction in the replication index (p > 0.0001). The present results confirm the genotoxic effects of RU on C. villosus lymphocytes in vitro, strongly suggesting that exposure to RU could induce DNA damage in C. villosus wildlife.